2020
DOI: 10.1146/annurev-publhealth-040119-094239
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stressors and Telomere Length: A Current Review of the Science

Abstract: A growing literature suggests that exposure to adverse social conditions may accelerate biological aging, offering one mechanism through which adversity may increase risk for age-related disease. As one of the most extensively studied biological markers of aging, telomere length (TL) provides a valuable tool to understand potential influences of social adversity on the aging process. Indeed, a sizeable literature now links a wide range of stressors to TL across the life span. The aim of this article is to revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 126 publications
2
67
1
Order By: Relevance
“…Leukocyte telomere length has been linked to immune cell dysfunction, various chronic diseases ( 60 ), and psychosocial stress [as summarized in ( 61 )]; telomere length has been suggested as a new tool for immunoepigenetics ( 62 ). A recent study from our lab using data from the National Health and Nutrition Examination Survey demonstrated that living in socioeconomically disadvantaged neighborhoods associated with shorter leukocyte telomere length among U.S. adults, indicating the potential impact of adverse neighborhood conditions on immune cells ( 63 ).…”
Section: Markers Of Social Position and The Immune Systemmentioning
confidence: 99%
“…Leukocyte telomere length has been linked to immune cell dysfunction, various chronic diseases ( 60 ), and psychosocial stress [as summarized in ( 61 )]; telomere length has been suggested as a new tool for immunoepigenetics ( 62 ). A recent study from our lab using data from the National Health and Nutrition Examination Survey demonstrated that living in socioeconomically disadvantaged neighborhoods associated with shorter leukocyte telomere length among U.S. adults, indicating the potential impact of adverse neighborhood conditions on immune cells ( 63 ).…”
Section: Markers Of Social Position and The Immune Systemmentioning
confidence: 99%
“…Although research has linked psychosocial stress to several markers of biological aging in humans, causal models that examine the specific mechanisms are lacking. For instance, a sizeable literature suggests that chronic stress exposure over the lifespan is associated with shortened telomere length; yet, only a few studies have prospectively tracked telomere length changes [17]. Several studies have also linked stressors such as caregiving, work-related stress, perceived stress, bereavement, and decreased feelings of closeness with parents during childhood to elevated oxidative stress and DNA damage and repair processes [6,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Kaufman et al observed that ten methylation sites interact with ACEs to predict cross-sectional measures of BMI and an additional six sites were found to exert a main effect in predicting BMI in youth [25]. In addition to influencing biological pathways, early life stressors may affect child behavioral patterns, such as eating, sedentary behavior, and sleep, which could potentially result in increased childhood obesity [4,5,[7][8][9][10][11][12]31].…”
Section: Plos Onementioning
confidence: 99%
“…These poor dietary and sleep practices are associated with obesity [6]. Similarly, ACE affects telomere length [7,8], which is associated with obesity [9,10]. In addition, food insecurity is associated with obesity in adults [11] and a recent study showed that a high cumulative adverse childhood experiences is associated with food insecurity [12].…”
Section: Introductionmentioning
confidence: 99%